Shaping Financial Landscape in India through Financial Inclusion and its Impact on Society (with focus on the Pradhan Mantri Jan Dhan Yojna) - et. al., Dr. Prachi Beriwala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Financial Inclusion is the timely provision or access of basic financial products to individuals and businesses especially the poor and the down trodden. It includes appropriate, affordable and timely financial products and services like banking, loans, insurance and equity. Economic security is the underlying principle behind financial inclusion without any bias or prejudice or unfair treatment and without taking into consideration the savings or the current financial position of the person. The scope of study of this paper also examines the similar situation on grossly Pan India basis taking into consideration the impact of Pradhan Mantri Jan Dan Yojna on society. Bringing underprivileged people under the financial umbrella has its own set of challenges like geography, inequalities of income and wealth, level of literacy and awareness, level of willingness and penetration and lack of governance and leadership which act as major impediments. This paper examines all such societal implications as well.